2015
DOI: 10.1016/j.joca.2015.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Human genome-wide expression analysis reorients the study of inflammatory mediators and biomechanics in osteoarthritis

Abstract: A major objective of this article is to examine the research implications of recently available genome-wide expression profiles of cartilage from human osteoarthritis (OA) joints. We propose that when viewed in the light of extensive earlier work this novel data provides a unique opportunity to reorient the design of experimental systems toward clinical relevance. Specifically, in the area of cartilage explant biology this will require a fresh evaluation of existing paradigms, so as to optimize the choices of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 83 publications
2
34
1
Order By: Relevance
“…[79][80][81] In contrast, the two cytokines for which we observed differences between the OAC-AM and NC-AM group -namely IL-6 and IL-8 -have been demonstrated to increase in late versus early shoulder OA. 82 Combined, these points of comparison of NC-AM to OAC-AM to human disease suggest that our OAC-AM system may be serving as a disease mimic for later stage OA than the NC-AM system.…”
Section: Discussioncontrasting
confidence: 60%
“…[79][80][81] In contrast, the two cytokines for which we observed differences between the OAC-AM and NC-AM group -namely IL-6 and IL-8 -have been demonstrated to increase in late versus early shoulder OA. 82 Combined, these points of comparison of NC-AM to OAC-AM to human disease suggest that our OAC-AM system may be serving as a disease mimic for later stage OA than the NC-AM system.…”
Section: Discussioncontrasting
confidence: 60%
“…Although both IL-1b and Fn-fs have been described as mediators of cartilage degradation in OA, our findings indicate that despite the contribution of both mediators, they are Fn-fs rather than IL-1b, which plays the major pathological role, in agreement with recent studies. 12 We showed that constitutive levels of ADAMTS-4, one of the main aggrecanases in cartilage destruction, were higher in OA than in HD. Interestingly, the higher levels of ADAMTS-7 in OA compared to HD, as well as the regulation of ADAMTS-12 by IL-1b and Fn-fs exclusively in SF from OA patients, suggest their potential as new therapeutic targets for the treatment of the disease.…”
Section: Q18mentioning
confidence: 80%
“…33 At the functional level, our results are in agreement with previous findings showing that ADAMTS 4 and 5 are not regulated by this cytokine in SF. 9,12,31 The role of IL-1b in OA is controversial, and the implication of other mediators, as cartilage ECM degradation products, seems to be more relevant in the pathology. 12 Despite that, the study of IL-1b, as a pleiotropic proinflammatory cytokine, also contributes to the knowledge of the mechanism involved in the disease.…”
Section: Synovial Fibroblasts In Osteoarthritismentioning
confidence: 99%
See 1 more Smart Citation
“…4,23-25 However, the available results are inconsistent and controversial. For example, Sandy et al 26 confirmed that the activation of matrix genes, but not IL-1β-responsive genes, played a critical role in the pathology of human OA. However, many results suggested that IL-1β was a significant modulator in cartilage degradation and IL-1β-induced cartilage degradation was involved in the regulation of miRNAs.…”
Section: Discussionmentioning
confidence: 99%